(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2025)
A study was conducted to evaluate the nature and properties of soil at different depths in lowland rice ecosystem of Zakiganj, Kulaura, Baniachong and Sarail Upazila of Bangladesh. The total 24 soil samples were collected from the above four sites covering six soil depth, viz. 0-10 cm, 10-20 cm, 20-40 cm, 40-60 cm, 60-80 cm and 80-100 cm. The mean value of pH was found 5.08 to 6.85 at the depth 0-40 cm and having much lower value in 40-100 cm depth at different sites. It indicates that soil of the sites are acidic in nature. The NPK and S content in studied areas were very low. Based on physico-chemical properties, the study revealed that soil nutrient levels are low in the study sites. The findings also indicate that upper soil layers (0-40 cm) are higher in potential fertility compared to the deeper layers (40-100 cm). Similar trends were observed in Baniachong and Sarail sites, where the upper soil layers exhibited higher fertility than the lower layers. However, an exception was found in Kulaura site hence the deeper soil layers (40-100 cm) had higher levels of soil organic carbon (SOC) and cation exchange capacity (CEC) than the upper layers. This difference is likely due to the clay illuviation in the lower depths where the prevalence of silty clay texture under imperfectly drained conditions of the soil. The above results underscored need to protect the surface and subsurface soil depths with proper management and care. J. biodivers. conserv. bioresour. manag. 10(2), 2024: 49-58